PENGARUH MASA SIMPAN DAN JENIS PENGIKAT GRAFTING TERHADAP KEBERHASILAN GRAFTING SIRSAK (Annona muricata) VARIETAS RATU - Tri Wahyu Hidayat (Biogenesis, 2018)
ABSTRACTIn nursery technology, the storage of scions always requires approriate optimization of shelf life and good packing This study aims to determine the effect of shelf life and storage materials on viability of soursop (Annona muricata) var. Ratu grafting by applying randomized factorial design with 2 factors: storage time and type of packing materials, with 3 times repeatation. The duration of storage time factor consist of 5 levels: 0 day, 3 days, 5 days, 1 week and 2 weeks meanwhile packing materials factor consist of 2 levels: parafilm and polyethylene. The highest survival rate was obtained at 0 day shelf life time and parafilm as storage material, whereas the lowest one was shown at 2 weeks storage with polyethylene as storage material.Keywords: Scion, Grafting, Storage, Packing Material, Soursop